1999
DOI: 10.1046/j.1365-2044.1999.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic practices of consultant anaesthetists: a survey in the North‐West region of the UK

Abstract: SummaryQuestionnaires were distributed to all 213 consultant anaesthetists in the North-West region of the UK with a response rate of 68%. These questionnaires were designed to assess the hygienic precautions taken to reduce the potential for transmission of infectious agents to and from the patients under their care. Face masks and gloves were always used by 35.2% and 14.5%, respectively, while only 36.4% washed their hands between cases. Most respondents have changed their practice since the recognition of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 30 publications
4
29
3
1
Order By: Relevance
“…One 1995 study [27] reported that only 58% of practicing anesthesiologists always washed their hands after contact with patients considered qlow riskq for HIV or HCV infection. A 1999 study [28] showed that only 14.5% of anesthesia providers always wear gloves and that only 36.4% wash their hands between cases [28]. The present study showed higher percentages: 52.6% of anesthesiologists and 70% of nurse anesthetists reported frequently or always washing their hands, and 65.3% and 82%, respectively, reported wearing gloves during anesthesia, but there were still 12.7% and 12% differences between handwashing and glove-wearing practices.…”
Section: Discussioncontrasting
confidence: 40%
“…One 1995 study [27] reported that only 58% of practicing anesthesiologists always washed their hands after contact with patients considered qlow riskq for HIV or HCV infection. A 1999 study [28] showed that only 14.5% of anesthesia providers always wear gloves and that only 36.4% wash their hands between cases [28]. The present study showed higher percentages: 52.6% of anesthesiologists and 70% of nurse anesthetists reported frequently or always washing their hands, and 65.3% and 82%, respectively, reported wearing gloves during anesthesia, but there were still 12.7% and 12% differences between handwashing and glove-wearing practices.…”
Section: Discussioncontrasting
confidence: 40%
“…The next step is to evaluate the extent to which our findings apply in clinical practice; the development and evaluation of interventions to reduce the risk of infection to patients from administering intravenous drugs during anaesthesia may then be appropriate. Interestingly, it has been shown previously that although most anaesthetists are aware of the need for aseptic techniques, many do not follow existing guidelines:25 55 56 our data may provide encouragement for doing so.…”
Section: Discussionmentioning
confidence: 75%
“…[14][15][16][17] A matter of particular concern is the infection risk due to unsafe injection practices that are associated with the use of single-dose vials for multiple patients [18][19][20] and the use of multi-dose vials. [6][7][8][9] International guidelines on preventing contamination of anaesthetic-associated medication 21,22 clearly state that preservative-free vials are single-patient, single-dose items.…”
mentioning
confidence: 99%